The Effect of Work Motivation and Work Discipline on Employee Performance at Bakso X Business - Teguh Setiawan Wibowo; Nurmala Sari; Najdah Thalib; Jusra Tampubolon; Febri Pramudya Wardani (PT PUSTAKA CENDEKIA PUBLISHER, 2025)
This study aims to examine the influence of work discipline and work motivation on employee performance in Bakso X. The research method used is of a quantitative type. The population is 30 employees who work at Bakso X. The instrument used to collect data is in the form of questionnaires. The data can be statistically analyzed using SPSS. The results showed that partially or simultaneously the test results had a significant value of 0.000. Based on this, it can be concluded that work discipline and work motivation have a significant effect on employee performance.